Credit Institutions in Improving the Village Economy Through Village-Owned Enterprises and Traditional Village Joint Enterprises in Kutuh Village, Bali - PRAMANA, Made Surya; PUTRA, I Putu Iwan Pramana; IDAWATI, Ida Ayu Agung (PT Keberlanjutan Strategis Indonesia, 2024)
Village development is one way to contribute to the country's economy. One way is to build a business unit that is able to maximize village potential and is able to manage village assets and resources in a sustainable manner. The aim of this research is to determine the role of Village Finance Institutions (LPD) in efforts to improve the performance of Manik Mas Village-Owned Enterprises ( BUMDes ) in Kutuh Village and Baga Utsaha Manunggal Traditional Village (BUMDA) in Kutuh Village, Badung Regency is in order to be able to improve the economy of Kutuh Village. This research is an explanatory qualitative research that uses primary and secondary data. The data in this research was collected using observation techniques, in-depth interviews and documentation. The data analysis technique uses NVivo 12 Pro software to generate related keywords among the data resulting from in-depth interviews with participants. The keywords obtained will be analyzed and conclusions will be made regarding the role of LPD in improving the economy of Kutuh Village through BUMDes and BUMDA. The results of the analysis show that the LPD of Kutuh Village collaborates with BUMDes and BUMDA in the form of providing fund savings services and providing credit with interest that has been approved by both parties. Apart from that, BUMDes and BUMDA contribute to the economy in Kutuh Village in the form of absorbing labor that only comes from the Kutuh Village community, developing and managing the village's tourism potential professionally and contributing income to Kutuh Village.